(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Water bodies are vital ecosystems that support various ecological processes and human activities. Understanding the seasonal variations in physio-chemical parameters of water bodies is crucial for assessing water quality and implementing effective management strategies. This study focuses on investigating seasonal variations in physio-chemical parameters in the Garga Reservoir, located in Bokaro, Jharkhand, India, over the period 2021-2023.The Garga Reservoir faces numerous challenges related to water quality degradation, including pollution from anthropogenic activities and natural processes. Monitoring physio-chemical parameters is essential for assessing water quality status and identifying potential stressors affecting the reservoir ecosystem. Seasonal variations in these parameters reflect dynamic changes in environmental conditions and provide valuable insights into the resilience and vulnerability of aquatic ecosystems.The study employs a longitudinal approach, collecting water samples from a designated sampling site (PSA-1) in the Garga Reservoir on a monthly basis over the two-year period. Physio-chemical parameters, including alkalinity, BOD, DO, E. Conductivity, hardness, pH, TDS, TS, and water temperature, are measured using standard methods. Statistical analyses and graphical representations are used to analyze temporal trends and correlations among the parameters.Analysis of the data reveals significant seasonal variations in physio-chemical parameters in the Garga Reservoir. Alkalinity, BOD, DO, E. Conductivity, hardness, pH, TDS, TS, and water temperature exhibit distinct seasonal patterns, influenced by environmental factors such as temperature, precipitation, and biological activity. These variations have implications for water quality, ecosystem health, and human well-being.The study provides valuable insights into the seasonal dynamics of physio-chemical parameters in the Garga Reservoir, highlighting the importance of long-term monitoring and management strategies for maintaining water quality and ecosystem integrity. By elucidating seasonal variations and identifying potential drivers of variability, the study contributes to informed decision-making and effective water resource management practices in the region.